Biological therapy in Psoriasis: An emphasis on its dermatologic adverse events - Pasita Palakornkitti (2022)
Objective: To report an overview of dermatologic adverse events (AEs) related to biologics used for psoriasis and compare common dermatologic AEs across different biologic classes. Data Sources: A comprehensive search in MEDLINE via PubMed from inception through June 9, 2021, was conducted. Study Selections: The selection process was performed independently by two reviewers. Studies were eligible if patients were diagnosed with plaque-type psoriasis, were treated with biologics, and had ≥ 1 dermatologic AE. Results: A total of 1023 records were identified, and 127 studies were included. The incidence of dermatologic AEs was 4.17% for tumor necrosis factor-α (TNF-α) inhibitors, 9.49% for interleukin (IL)-12/23 inhibitor, 12.40% for IL-17 inhibitors, and 7.37% for IL-23 inhibitors. Biologic-related dermatological AEs can be classified into allergic skin reactions, inflammatory skin diseases, skin infections, skin neoplasms, and miscellaneous AEs. An evident class effect was observed. Skin neoplasms (1.45%), mainly nonmelanoma skin cancer (1.36%), predominated among TNF-α inhibitors. Allergic skin reactions (6.25%) were frequently reported with IL-12/23 inhibitor. During treatment with IL-17 inhibitors, skin infections (5.01%) were common, and the most common was driven by mucocutaneous candidiasis (4.85%). Inflammatory skin disease (2.32%), mainly eczematous eruptions (0.84%), dominated in IL-23 inhibitors. Conclusions: A predominance of specific dermatologic AEs appears in distinct biologic classes due to their different specific targets of action. Further study is needed to understand the mechanisms of these potential AEs, which will help in their management.